Can diagnostic and imaging recommendations from the 2011 AAP UTI guidelines be applied to infants <2 months of age?. Issue 6 (December 2022) - Walton, Ryan F.; Shannon, Rachel; Rague, James T.; Chu, David I.; Rosoklija, Ilina; Carter, Laura C.; Johnson, Emilie K.
Summary: Introduction: In 2011, the American Academy of Pediatrics (AAP) published guidelines regarding diagnosis and management of children 2-to-24-months-old with initial febrile urinary tract infection (fUTI). Available data were insufficient to determine whether evidence from studies of 2-to-24-month-olds applies to those <2-months-old, so they were excluded. Objective: This study aimed to 1) compare demographic, clinical, imaging and outcomes between patients <2-months-old and those 2-to-24-months-old hospitalized with fUTI, and 2) assess whether diagnostic and imaging recommendations of the AAP 2011 guidelines apply to those <2-months-old. Study design: A cohort study of patients ≤24-months-old hospitalized at a children's hospital with fUTI from 2016 to 2018 was conducted. Data were collected via a prospectively generated electronic medical record note template, supplemented with retrospective chart review. Primary outcomes included differences in demographics, clinical presentation, urine culture results, and imaging utilization/results by age group. Secondary outcomes included surgical procedures, UTI recurrence, and 90-day all-cause readmissions and emergency department (ED) revisits. Univariate and bivariate statistics were utilized to compare age groups. Results: Overall, 137 patients were included (median age 70 days, 55.5% male [92.1% uncircumcised], 53.3% Hispanic/Latino, 89.8% 1st fUTI). There were no demographic differences between groups, except children <2-months-old were more frequently male (71.2 vs 43.6%, p = 0.002). The Summary Table compares clinical factors and imaging utilization by age. There were no differences in urinalysis or urine culture results between groups. Patients <2-months-old had shorter fever duration, lower maximum temperature, and lower white blood cell counts. Voiding cystourethrograms (VCUGs) were recommended and obtained more frequently in patients <2-months-old, but there were no differences in renal and bladder ultrasound (RBUS) or VCUG results between age groups. There were no differences in UTI recurrence (13.6% of <2-months-old vs 14.1% of 2-to-24-months-old, p = 1.00) or fUTI recurrence (13.6 vs 7.7%, p = 0.40) within 1 year, 90-day readmission (6.8 vs 6.4%, p = 1.00), or 90-day ED revisit (22.0 vs 20.5%, p = 1.00). Discussion: There were minimal differences between the <2-months-old and 2-to-24-months-old age groups in demographics, laboratory (including microbial) or imaging results, or clinical outcomes. Patients <2-months-old were more frequently male and less ill. These data support applying urinalysis and urine culture diagnostic criteria, and universal RBUS, from the AAP guidelines to patients <2-months-old. Given utilization differences, applicability of VCUG guideline recommendations requires further clarification for patients <2-months-old. Conclusion: Laboratory testing and RBUS recommendations from the AAP guidelines may be safely applied to infants <2-months-old. Further studies are needed to clarify optimal VCUG recommendations.